Slaughterhouse-five [videorecording (DVD)] - Hill, George Roy, 1921-2002; Sacks, Michael; Leibman, Ron; Perrine, Valerie; Vonnegut, Kurt (Universal Pictures : Distributed by Universal Studios Home Entertainment, 2004)
Billy Pilgrim has become unstuck in time. An otherwise typical soldier in WWII, without warning, he jumps back and forth in his life with no control over where he is going next. Sometimes he is an ophthalmologist at home in suburbia; deep in World War II Europe, surviving the Allied bombing of Dresden; on the planet Tralfamadore, being held captive by aliens in an intergalactic zoo--accompanied by a porn star. In the end, he learns that the many tragic and sometimes funny ironies of life--the randomness of tragedy, the cruelty and senselessness of war, and man's complete lack of control over his fate--remain constant.